Sistem Jakarta Pendukung Keputusan Pemilihan Siswa-Siswi Terbaik dengan Metode SAW (Simple Additive Weigthing) pada Sekolah SMP Negeri 16 - Adelvita Buik Bria; Rouli Doharma (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The selection of the best students in schools is essential to recognize both academic and non-academic achievements and to motivate other students to improve their skills. SMP Negeri 16 Jakarta requires an objective decision support system to select the best students based on predefined criteria. This study aims to design and implement a decision support system using the Simple Additive Weighting (SAW) method to facilitate the selection of the best students at SMPN 16 Jakarta. The SAW method is chosen due to its capability to accommodate multiple criteria through weighting and ranking for each alternative. The research process involves observation, interviews, and documentation, which are then used to determine primary criteria such as academic achievement, social skills, and participation in school activities. The findings show that the application of the SAW method enables a more accurate and objective selection of the best students by ranking based on the final score of each criterion. This system is expected to assist SMPN 16 Jakarta in making more structured decisions and supporting educational quality improvement.